Expanding Opportunities for Science, Technology, Engineering and Mathematics Subjects Teaching and Learning: Connecting through Comics. - ADNAN, Mazlini; ABDULLAH, Jafri Malin; MD IBHARIM, Laili Farhana; Wee Hoe, TAN; JANAN, Dahlia; ABDULLAH, Norazilawati; IDRIS, Noorzeliana; ABDUL WAHAB, Amila Saliza; OTHMAN, Ahmad Nizam; HASHIM, Mohd Ekram Alhafis; MD SAID, Nooraishah; ADNAN, Rosni; et al. (Malaysian Journal of Medical Sciences)
This study presents the results of a year-long project focused on analysis and reflection on working with comics by Year One students in Hulu Langat districts. This study presents the use of science, technology, engineering and mathematics (STEM) comics to help children understand certain physical phenomena and try to make students interested in mathematics and science subject. Thirteen excellent teachers of science and mathematics from the Hulu Langat district were involved in the analysis of syllabus Year One science and mathematics subjects and the preparation of scripts while the STEM comic illustrator was created by two lecturers from the Faculty of Art, Computing and Creative Industry from Universiti Pendidikan Sultan Idris, Perak Malaysia. The study is based on observations of changing perception of phenomena by children as a result of the use of comics. As a result, a STEM comic that contains ten series for Year One science and mathematics subjects has been successfully developed. This comic is expected to attract and enhance the achievement of Year One students in science and mathematics. Implication of this study, STEM comics can be used by teachers as science and mathematics teaching aids. Comics are proven to be a modern pedagogical strategy, which is starting to gain its popularity in teaching about mathematics and science. Comics can be very helpful tools in making science and mathematics concepts interesting, fun learning and comprehensible for a Year One children.